Evaluation of Antioxidant Capacity of Solanum sessiliflorum (Cubiu) Extract: An In Vitro Assay - Diego Rocha de Lucena Herrera Mascato; Janice B. Monteiro; Michele M. Passarinho; Denise Morais Lopes Galeno; Rubén J. Cruz; Carmen Ortiz; Luisa Morales; Emerson Silva Lima; Rosany Piccolotto Carvalho (Journal of Nutrition and Metabolism)
Cubiu is a vegetable of Solanaceae family, native to the Amazon, which is widely distributed through Brazil, Peru, and Colombia. It is used in food, medicine, and cosmetics by native populations. Research has shown that cubiu extracts have antioxidant activities with great biological relevance. We performed a phytochemical screening to identify the main chemical groups that could confer antioxidant activity to this extract. Several tests and qualitative precipitation specific staining for major classes of secondary metabolites were used. Antioxidant capacity in vitro tests (DPPH and ABTS) were also used to assess the extract’s ability to sequester free radicals of 70% hydroethanolic and aqueous extracts of cubiu flour. Alkaloids, organic acids, phenols, flavonoid glycosides, and coumarins were found in the hydroethanolic extract while the aqueous extract presented anthocyanins, gums, tannins and mucilage, amino groups, and volatile and fixed acids. For in vitro tests, the IC50 value obtained in the DPPH assay was 606.3 ± 3.5 μg/mL while that for the ABTS assay was 290.3 ± 10.7 µg/mL. Although cubiu extracts present chemical compounds directly related to antioxidant activity, our results show that it has a low antioxidant activity. Additional studies will be needed to isolate and characterize specific compounds to further assess antioxidant activity.